2014
DOI: 10.1002/acr.22109
|View full text |Cite
|
Sign up to set email alerts
|

Primary Antiphospholipid Syndrome–Associated Diffuse Alveolar Hemorrhage

Abstract: Objective. Diffuse alveolar hemorrhage (DAH) is an uncommon complication of primary antiphospholipid syndrome (APS). We aimed to describe the clinical characteristics, treatment, and outcomes of primary APS-associated DAH in a single center. Methods. We conducted a retrospective review of all adults with primary APS-associated DAH evaluated at Mayo Clinic over a 15-year period. DAH was defined as bilateral pulmonary infiltrates and bronchoalveolar lavage (BAL) fluid documenting progressively bloody returns and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
61
0
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(72 citation statements)
references
References 34 publications
3
61
0
8
Order By: Relevance
“…In our case, owing to recurrent disease and a high risk of new DAH episodes, we decided to start with CYC treatment. Although there are currently no randomized trials to support any recommendations regarding the choice of a steroid-sparing drug, CYC has been used effectively in vasculitides such as granulomatosis with polyangiitis and is suggested, along with rituximab, to be one of the most effective steroid-sparing agents in this setting [3,4,10]. However, CYC www.journals.viamedica.pl treatment failed to maintain remission in our patient.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…In our case, owing to recurrent disease and a high risk of new DAH episodes, we decided to start with CYC treatment. Although there are currently no randomized trials to support any recommendations regarding the choice of a steroid-sparing drug, CYC has been used effectively in vasculitides such as granulomatosis with polyangiitis and is suggested, along with rituximab, to be one of the most effective steroid-sparing agents in this setting [3,4,10]. However, CYC www.journals.viamedica.pl treatment failed to maintain remission in our patient.…”
Section: Discussionmentioning
confidence: 67%
“…Yachoui et al [4] published a case series report in which only one out of six patients subjected to lung biopsy showed neutrophilic infiltration, while the remaining five presented as bland hemorrhage [4]. Others have underlined [2] that neutrophilic interstitial infiltration alone, [3,4,10,11] without perivascular or vascular infiltrates does not allow for recognizing vasculitis. However, lack of these features does not allow for a virtual ruling out of vasculitis because histological findings may vary depending on both the lung region and the activity of the disease [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other immunosuppressive agents, such as cyclophosphamide, azathioprine, and mycophenolate mofetil, have been used in an attempt to achieve complete remission. Additionally, some case reports noted that intravenous immunoglobulin treatment (4,12,16), plasmapheresis (13), and rituximab (15, 16) may be effective for patients who do not respond to corticosteroids. Cartin-Ceba et al reported that immunosuppression with either cyclophosphamide or rituximab may have a higher likelihood of success (16).…”
mentioning
confidence: 99%
“…Additionally, some case reports noted that intravenous immunoglobulin treatment (4,12,16), plasmapheresis (13), and rituximab (15, 16) may be effective for patients who do not respond to corticosteroids. Cartin-Ceba et al reported that immunosuppression with either cyclophosphamide or rituximab may have a higher likelihood of success (16). In the present case, DAH responded well to corticosteroids and is currently being controlled without other immunosuppressive agents.…”
mentioning
confidence: 99%